Identifying the environmental hotspots in the production of xylitol to be used as a phase change material - da Silva Santos, Humberto; Guillén Lambea, Silvia (Jornada de Jóvenes Investigadores del I3A, 2024)
The objective of this work is to investigate the environmental hotspots in the production of the phase change material xylitol. Results showed that biotechnological production (BP) has lower environmental impacts than chemical production (CP). Energy is the environmental hotspot for the BP, and energy and nickel for the CP.